Theory and Practice of Mathematics and Computer Science Vol. 7 - Ferreira, M. A. M. (2021)
This book covers key areas of mathematics and computer science. The contributions by the authors include susceptibility, impulse response function, Hilbert-transform, Fourier transform, conjugate Fourier transform, convolution, causal systems, non-causal systems, analyticity, Kramer-Kronigs relation, relaxation, retardation, epidemics model, hyper geometric function, inequalities, communicable diseases, Concept Lattice, formal concept, frequent pattern, association rules, landmark, Convection-diffusion-reaction equation, alternating-direction implicit scheme, traveling wave solutions, linear and nonlinear differential equations, best proximity point, Geraghty function, Geraghty contraction, series expansion, fluid models, intermolecular potential model, integral Equations, Timoshenko system, exponential stability, distributed delay, pattern recognizer, frame homomorphism, quotient frames, matrix inversion, matrix multiplication, recursive algorithm, matrix order expansion, matrix order condensation, Jackson operator, generalized modulus of smoothness, K-function. This book contains various materials suitable for students, researchers and academicians in the field of mathematics and computer science.